Guidance of the resonance energy flow in the mechanism of coupled magnetic pendulums - Pilipchuk, Valery N.; Polczyński, Krystian; Bednarek, Maksymilian; Awrejcewicz, Jan (Elsevier, 2022)
This paper presents a methodology of controlling the resonance energy exchange in mechanical system consisting of two weakly coupled magnetic pendulums interacting with the magnetic field generated by coils placed underneath. It is shown that properly guided magnetic fields can effectively change mechanical potentials in a way that the energy flow between the oscillators takes the desired direction. Studies were considered by using a specific set of descriptive functions characterizing the total excitation level, its distribution between the pendulums, and the phase shift. The developed control strategies are based on the observation that, in the case of antiphase oscillation, the energy is moving from the pendulum subjected to the repelling magnetic field, to the oscillator under the attracting field. In contrast, during the inphase oscillations, the energy flow is reversed. Therefore, closed-loop controller requires only the information about phase shift, which is easily estimated from dynamic state signals through the coherency index. Advantage of suggested control strategy is that the temporal rate of inputs is dictated by the speed of beating, which is relatively slow compared to the carrying oscillations.
Keywords: resonance energy exchange; magnetic pendulums; beating control; coupled oscillators; nonlinear dynamics; magnetic field; rezonansowa wymiana energii; wahadła magnetyczne; kontrola bicia; sprzężone oscylatory; dynamika nieliniowa; pole magnetyczne